Sudan : Detailed Assessment of Observance of the AML/CFT Standard - International Monetary Fund (World Bank, Washington, DC, 2021)
Crime statistics over past two years, and meetings with the competent authorities, reveal there is a general increase in the level of crimes involving financial gains, people and drug smuggling as well as customs duty evasion. Indicators suggest that this criminality is of an organized nature. There are also 3 to 4 cases of serious fraud per year; the value of each individual case is more than the current capitalization of several domestic banks, which poses obvious risks to the stability and soundness of the financial sector. This report provides a summary of the evaluation of the anti-money laundering and combating the financing of terrorism (AML/CFT) measures in place in Sudan as at the date of the on-site visit. It describes and analyzes those measures, and sets out Sudan's levels of compliance with the recommendations. It also provides recommendations on how certain aspects of the system could be strengthened.